A Cable-Passive Damper System for Sway and Skew Motion Control of a Crane Spreader - La Duc Viet; Youngjin Park (Shock and Vibration)
While the crane control problem is often approached by applying a certain active control command to some parts of the crane, this paper proposes a cable-passive damper system to reduce the vibration of a four-cable suspended crane spreader. The residual sway and skew motions of a crane spreader always produce the angle deflections between the crane cables and the crane spreader. The idea in this paper is to convert those deflections into energy dissipated by the viscous dampers, which connect the cables and the spreader. The proposed damper system is effective in reducing spreader sway and skew motions. Moreover, the optimal damping coefficient can be found analytically by minimizing the time integral of system energy. The numerical simulations show that the proposed passive system can assist the input shaping control of the trolley motion in reducing both sway and skew responses.